A sensitive and selective fluorescent probe for hydrazine with a unique nonaromatic fluorophore. Issue 10 (4th February 2020) - Liu, Jian; Li, Tao; Wang, Shun; Qi, Qingrong; Song, Hang; Li, Zicheng; Yang, Li; Huang, Wencai
Abstract : A novel fluorescent probe for hydrazine with low detection limit and large Stokes shift was developed. Abstract : To achieve sensitive, selective and facile detection of hydrazine in environmental and biological systems, a fluorescent probe (Che-Dcv ) with a unique nonaromatic fluorophore was developed. Upon hydrazine addition in 20% DMSO–PBS buffer (pH = 7.4, 10 mM, v/v) at room temperature, the probe displayed a strong emission at 496 nm along with a color change from brown-red to yellow. The response was attributed to the reaction of dicyanovinyl groups with hydrazine to afford hydrazone, which was supported by 1 H NMR and HRMS. The detection limit of Che-Dcv for hydrazine was estimated to be as low as 1.08 ppb and good selectivity over amines including hydroxylamine was observed. Then, the potential of probe-coated test papers to detect hydrazine in solution and vapor phase was demonstrated. Moreover, the bioimaging of hydrazine in living H1975 cells was performed successfully.